Fabrication and evaluation of solidified nanoemulsion designs for systemic delivery of atorvastatin through the lung - Muhammad Danish Saeed; Kifayat Ullah Shah; Asif Nawaz; Faiqa Falak Naz; Amira Metouekel; Gamal A. Shazly; Musaab Dauelbait (Scientific Reports)
Abstract To improve the solubility of atorvastatin and overcome the stability issues of liquid nanoemulsion, the current study aimed to synthesize solidified SNEDDS particles with aerodynamic diameter of ≤ 3 μm. The simple and chitosan-decorated liquid SNEDDS were dried by spray drying method and evaluated for their physicochemical properties, release characteristics and aerodynamic performance. A single dose pharmacokinetic study was performed in rabbits to establish the therapeutic performance of solidified nanoemulsion with respect to LIPITOR. The liquid SNEDDS were efficiently dried with pectin (1% w/w). The chitosan decorated solidified SNEDDS (SF10) have small particle size (2.02 μm), higher tapped density (0.733 g/cm3) and smooth surface as compared to uncoated solidified SNEDDS (SF8). The chitosan coated SNEDDS had higher drug content and significantly lower roughness than uncoated SNEDDS (student t-test; p ≤ 0.01). The uncoated SNEDDS exhibited significantly higher burst drug release as compared to the chitosan coated SNEDDS due to the porous structure, amorphous nature and small size of its associated nanoemulsion. The solidified nanoemulsion had relatively lower MMAD (1.0 to 1.5 μm) that supports higher FPF values of 45–54% for the uncoated SNEDDS and chitosan coated SNEDDS, respectively. The pharmacokinetic study revealed that the solidified SNEDDS are superior with respect to its bioavailability being 1.5 times higher than LIPITOR.